2023
DOI: 10.3350/cmh.2022.0181
|View full text |Cite
|
Sign up to set email alerts
|

Baveno-VII criteria to predict decompensation and initiate non-selective beta-blocker in compensated advanced chronic liver disease patients

Abstract: Background/Aims: The utility of Baveno-VII criteria of clinically significant portal hypertension (CSPH) to predict decompensation in compensated advanced chronic liver disease (cACLD) patient needs validation. We aim to validate the performance of CSPH criteria to predict the risk of decompensation in an international real-world cohort of cACLD patients.Methods: cACLD patients were stratified into three categories (CSPH excluded, grey zone, and CSPH). The risks of decompensation across different CSPH categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…Compared to the PREDESCI study, and as discussed by the authors, the risk of first hepatic decompensation was considerably lower (24% in the placebo group of the PREDESCI study vs. 13.3% of CSPH ruled-in patients from this study) 23 . While this can be explained by differences in the underlying patient population (patients with CSPH vs. CSPH ruled-in by NIT; only active HCV infection in the PREDESCI trial vs. only cured HCV patients in the present study), this also influences the numberneeded-to-treat (NNT) for NSBB, which might be even lower than in the study by Wong and colleagues 9 (proposed NNT of 27-50). This calls for a 'non-invasive' PREDESCI trial to re-ensure our current clinical practice using contemporary patients.…”
Section: Editorialcontrasting
confidence: 61%
See 1 more Smart Citation
“…Compared to the PREDESCI study, and as discussed by the authors, the risk of first hepatic decompensation was considerably lower (24% in the placebo group of the PREDESCI study vs. 13.3% of CSPH ruled-in patients from this study) 23 . While this can be explained by differences in the underlying patient population (patients with CSPH vs. CSPH ruled-in by NIT; only active HCV infection in the PREDESCI trial vs. only cured HCV patients in the present study), this also influences the numberneeded-to-treat (NNT) for NSBB, which might be even lower than in the study by Wong and colleagues 9 (proposed NNT of 27-50). This calls for a 'non-invasive' PREDESCI trial to re-ensure our current clinical practice using contemporary patients.…”
Section: Editorialcontrasting
confidence: 61%
“…In a recent issue of Clinical and Molecular Hepatology, Wong and colleagues 9 Singapore. Notably, this multi-ethnic cohort included predominantly cured HCV (56%) or suppressed HBV (21%) patients; median LSM was ~24kPa at study inclusion and patients were followed for 40 months.…”
Section: Editorialmentioning
confidence: 99%
“…There are several limitations of the study by Jun et al 8 . Among these, are the variability in patients' characteristics and clinical practices across the different institutions, the retrospective nature of the study introduces particularly information bias, not accounting for missing information in patients' records.…”
mentioning
confidence: 93%
“…Recently, a study was conducted to validate the recompensation criteria of the Baveno VII [ 8 ], but few studies thus far have validated the CSPH criteria based on a non-invasive assessment. At an opportune time, Wong et al [ 9 ] conducted a large-scale multinational study to validate the CSPH criteria based on TE and platelet count in cACLD patients (TE value ≥10 kPa). In this study, CSPH was classified into four groups.…”
mentioning
confidence: 99%
“…Wong et al [ 9 ] showed that the definite CSPH (TE >25 kPa) criterion can effectively predict liver decompensation and liver-related events. In particular, the fact that any patient with the excluded CSPH condition did not experience decompensation augments the reliability of the exclusion criteria.…”
mentioning
confidence: 99%